Parent–Adolescent Relationship Qualities and Adolescent Adjustment in Two‐Parent African American Families. Issue 4 (24th August 2013) - Stanik, Christine E.; Riina, Elizabeth M.; McHale, Susan M.
Abstract : Using multi‐informant data from 134 two‐parent African American families, the goals of this study were to (a) describe parent–adolescent warmth and shared time as a function of parent and youth gender and (b) assess links between these indices of relationship quality and adolescent adjustment. Mixed‐model ANCOVAs revealed that mothers reported warmer relationships with adolescents than fathers, and both parents reported warmer relationships with younger versus older offspring. Interparental differences in time spent with sons and daughters and older and younger siblings were also found. Tests of multilevel models indicated that greater maternal warmth was associated with fewer depressive symptoms and less risky behavior for sons, and more paternal warmth and shared time with fathers were associated with less risky behavior in youth. Discussion highlights the utility of cultural ecological and family systems perspectives for understanding parent‐adolescent relationships and youth adjustment in African American families .